Tariqah Ta’lim al-Lughah al-‘Arabiyyah li Firqah al-Khassah al-Lughawiyyah fi Tarqiyyati Maharah al-Kalam al-‘Arabiy - Khulwani Khulwani; Hayyik Nur Hakiim (Postgraduate of IAIN Metro Lampung Indonesia, 2020)
Lately we have found many educational institutions in Indonesia give more attention to learning Arabic. TMI Al Amien Prenduan, one of the educational institutions that gives more attention to foreign languages, especially Arabic, is known by its motto